THE CULTURE OF ETHNIC MINORITIES: PROBLEM ANALYSIS AND SYNTHESIS OF NOOSPHERIC - Evgeniy S. Goldschmidt; Vladimir V. Poddubikov (Открытое образование (Москва), 2016)
The critical condition of the South-West Siberia indigenous ethnic groups and the dominant society interaction was considered on the basis of multidisciplinary ethnological and socio-psychological research. The paper describes the phenomena of traditional values degradation, their inversion, as well as indigenous peoples representatives’ hyper-compensatory forms of adaptation, the phenomenon of imbalance activation of the cerebral hemispheres and the brain asymmetry change. It’s proposed to take into account the interacting communities’ archetypic features, their psychological maturity and indicators of brain asymmetry while managing the interaction between ethnic minority groups and the dominant society, as well as their mutual adaptation. Such context of the problems, this paper discusses, shows the signs of noosphere orientation of synthetic culture and practice which currently forming and developing. The research provided this paper with the basic data has received the financial support from Russian Foundation for Humanities (Project No 15-01-18098).